Synergistic effect of residual stress and phosphorus grain-boundary segregation on embrittlement of coarse-grained heat-affected zone in a novel Ni-Cr-Mo reactor pressure vessel steel. (February 2022) - Wang, T.C.; Guo, Y.; Chen, X.M.; Wang, K.; Song, S.H.
Highlights: Residual stress and P segregation synergistically affect ductile-brittle transition. P segregation plays an important role in embrittlement of heat-affected zones. A mechanism diagram is established for the synergistic effect. Abstract: SA508Gr.4N steel is a novel Ni-Cr-Mo low-alloy steel for the new-generation reactor pressure vessel. Herein, a coarse-grained heat-affected zone (CGHAZ) in a P-doped SA508Gr.4N steel is simulated using Gleeble thermal cycling simulation with a peak temperature of 1320 ℃ under a heat input of 100 kJ cm −1 . For the as-simulated specimen, due to the synergistic effect of high residual stress and P grain-boundary segregation, the fracture appearance changes in the order of ductile fracture to intergranular fracture, and then to cleavage fracture with decreasing impact temperature. With the residual stress relieved by annealing at 620 ℃, the specimen toughens to a certain extent even after ageing at 560 ℃, causing a decrease in ductile-to-brittle transition temperature (DBTT), although the boundary cohesion declines to a certain degree owing to the increase of P segregation. Simultaneously, the intergranular-to-cleavage fracture transition temperature (ICFTT) shifts to a lower temperature below –190 ℃, enabling the specimen to exhibit intergranular fracture even at −190 ℃. With the ageing temperature lowered to 500 ℃, the boundary segregation of P is raised to a high level, leading to a large increase in DBTT and a further decrease in ICFTT. Accordingly, the synergistic effect of residual stress and P boundary segregation affects the fracture nature of CGHAZ, thereby making fracture appearance have different characteristics. A mechanism diagram for the above effect is proposed based on the experimental results.